A Novel Method to Prevent Extreme Whole-body Vibration to Mine Workers in Underground Coal Mine Due to Heavy Earth Moving Machineries - Verma T.; Gupta S.; Jain C. (My University, 2025)
The dangers of whole-body vibration (WBV) are well-known in today's mining industry. This study aims to use a mobile and user-friendly device for measuring WBV exposure and suggests a Time to Action (TA) and Time to Switch (TS). Raw vibration data were collected using the iPod firmly taped on the operator's seat throughout the sample time by the iPod-based iOS application 'WBV'. The measured values were compared with the ISO 2631-1 standard, WBV readings in a few machines and found above the Health Guidance Caution Zone (HGCZ). For 8 hours shifts, Acceleration (A (8)) and Vibration dose value (VDV (8)) in Load haul dump (LHD) and Man Riding vehicle (MRV) were in the risk zone. Finally, the Time to Action and Time to Switch were calculated for each machinery. Mine machinery operators are also prone to WBV beyond permissible limits, so using the results from this study, some appropriate managerial decisions are suggested. © 2023 IEEE.